Crown dilacerations - Two case reports (Nigerian Dental Journal, 2011)
Crown dilaceration is a relatively abnormal clinical finding when compared to root dilacerations. The incidence of crown dilacerations is stated to be as low as 3%. This report presents two cases of crown dilacerations in two different locations. A brief review of the literature pertinent to the condition, and the clinical and radiological features of this rarer entity are discussed.
Keywords: Dilacerations; Trauma; Lateral incisor; Premolar